Dr. Dunbar's Sirius puppy training [videorecording (DVD)] - Dunbar, Ian, 1947-; Bluford, Martin; Toth, Beth M. (James & Kenneth Publishers, 2006)
Includes obedience commands, housetraining, and behavior and temperament training in a comprehensive program developed for puppies less than 18 weeks old. Not intended for the training of adolescent and adult dogs, nor for the treatment of existing behavior problems in these dogs. Emphasizes family participation with daily handling and gentle exercises to teach basic obedience commands and overcome biting, barking and housetraining behavioral problems.